RNA Splicing Aberrations in Hereditary Cancer: Insights from Turkish Patients - Seda Kilic; Ozge Sukruoglu Erdogan; Seref Bugra Tuncer; Betul Celik Demirbas; Zubeyde Yalniz Kayim; Hulya Yazici (Current Issues in Molecular Biology)
The process of RNA splicing is fundamental in contributing to proteomic diversity and regulating gene expression. Dysregulation of splicing is associated with various human disorders, including cancer. Through functional studies, this study sought to examine the potential impact of seven variants within six inherited cancer-related genes on RNA splicing patterns in Turkish cancer patients. Upon detecting variants using Next-Generation Sequencing (NGS), we used Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) and Sanger sequencing to elucidate the effects of these variants on splicing. Three of the seven variants demonstrated no discernible effect on RNA, while four exhibited pathogenic characteristics. Specifically, the variants APC c.532-1G>A rs1554072547, BRCA1c.4358-3A>G rs1567779966, BRCA2c.7436-1G>C rs81002830 and MSH3c.1897-1G>A rs1744149615 were identified as pathogenic, while the variants BLMc.4076+4T>G rs183176301, RB1c.2489+2T>C rs1555294636 and RB1c.1050-2A>G rs? were found to be benign from a splicing perspective. These findings highlight the importance of verifying the precise consequences of splice-site variants through experimental analysis, given their potential implications for genetic disorders and cancer predisposition. This research contributes to the understanding of splice-site variants in inherited cancer predisposition, particularly among Turkish cancer patients. It emphasizes the necessity for further exploration into the mechanisms and functional consequences of alternative splicing for potential therapeutic interventions in cancer.